The Effect of Leverage, Corporate Social Responsibility (CSR), Capital Structure, and Intellectual Capital on Financial Performance of Companies - Ninggih Annisa Daniswara; Indra Kusumawardhani; Windyastuti Windyastuti (AIBPM Publisher, 2021)
The main purpose of the entity is to increase the value of the entity itself. The increase in the value of the entity is of course also directly proportional to the increase in the performance of an entity. One of the values of a company can be seen from its financial performance. The goal of this research is to find out the effect of leverage, corporate social responsibility (CSR), capital structure, and intellectual capital on financial performance of companies. The sample consisted of 67 respondents which are listed in the Kompas 100 Index for the period 2017 - 2019. In this research, purposive sampling was used to select the sample. To analyze the data, researchers were using multiple linear regression analysis. The results show that intellectual capital and leverage both affect company’s financial performance. On the other hand, capital structure and CSR have no effect on company’s financial performance.